IMPROVING STUDENTS’ SPEAKING SKILLS BY DIGITAL STORYTELLING TECHNIQUE IN PANDEMI COVIC-19 - Nurfadilah Ginting; Narma A. Situmorang; Afrilia Aries Tanti; Dara Saras Putri; Sri Ninta Tarigan (English Language Teaching Prima Journal (ELT), 2021)
Abstract The aim of this research is to determine whether using digital storytelling strategy can help students develop their speaking skills, as well as to clarify how using a digital storytelling strategy can help students improve their speaking skills. Classroom action research was used to perform this analysis, which was completed in two cycles. The research subject is 10 students, they are from XI class of SMK Panca Budi Medan in school years 2020/2021. The research data was taken from quantitative data, were collected by giving the retelling stories tests. The mean score for the pre-test was 42,4, post-test I was 62, post-test II was 80. It also evident from the percentage of the students who passed the Minimum Mastery Criterion – (KKM) score above75. In the pre-test, there were 20% of the students who got score above 75 % In post-test I, there was 40%, meanwhile post-test II, there were 80%. It can be concluded that digital storytelling strategy worked effectively to help students in improving their speaking skills. this research found that using a digital storytelling technique boosted students' speaking abilities significantly. It was suggested that english teachers can apply digital storytelling strategy as one of the alternatives in teaching speaking skills. Keyword: Digital Storytelling Technique, Improving, And Speaking